World without walls - Wong, Ayman Rashdan (Patriots Publication Sdn Bhd, 2020)
These three expressions are the factors that can break the wall that brings differences among human in the world in reaching agreement and understanding between one another. The knowledge about international geopolitics is the key to the survival of country and nations, and knowledge gained must be based on the principles of Realism, Diplomacy and Patriotism.These principles will be explained through 50 articles that have been written by the writer over the past year on geopolitics and international relations.